Alasan Permohonan Kasasi Oleh Penuntut Umum Terhadap Putusan Lepas Dari Segala Tuntutan Hukum Dalam Perkara Penipuan - Ardhadedali Aulia Putri (Sebelas Maret University, 2017)
The purpose of this research is to understand the reason of Prosecutor to apply a cassation and the consideration of the Supreme Court’s Judge in examine and judging the embezzlement case. The public prosecutor evaluate that the judge is wrong at judging the embezzlement case. Case reviewed at Supreme Court’s Verdict Number 251 K/ Pid/ 2015 was case of bedrog. The defendant gave offer for invest in her business and promise to give the profit about 4%. Yogyakarta District Court’s Judge evaluate the act that committed by the defendant is including civil sphere because the judge just examined the agreement, whereas since the beginning the defendant already had a bad faith when she asked for more fund with the reason that she didn’t have money for return the last fund. The agreement made since the second time, while on the first there was no agreement yet. The results showed that the public prosecutor uses alternative form of indictment with bedrog and embezzlement elements. The Judge of Yogyakarta District Court decided an onslag verdict on the basis of consideration that the defendant was right proven to do the act but it’s not a criminal act. The public prosecutor submit the cassation application with reasons that the judge didn’t watch the facts in court and ignore the argumentation. The public prosecutor’s reason in cassation application against onslag verdict in bedrog is that the law was not occurred necessarily and it’s consistent with the Article 253 of Criminal Codes Procedures about the reason of Cassation application. Consideration of the Supreme Court’s Judge in examine the cassation application for onslag verdict in bedrog is based on the facts on the court and the Article 256 juncto 193 of Criminal Codes Procedures about cassation. Keywords: Bedrog, Embezzlement, Cassation Reasons, Evidences, Consideration of The Judge.